The Effectiveness of Emotion Regulation Training to Increase Happiness in Adolescents in Orphanages - Rina Mirza; Purba, Rany Seni Tani; Khaliza, Nazwa Maura; Sinabutar, Silvia Natalia; Achmad Irvan Dwi Putra (Universitas PGRI Yogyakarta, 2026)
Based on the model of emotion regulation (Gross, 1998), the ability to manage emotional responses is very important for achieving subjective well-being and happiness. Adolescents in orphanages are vulnerable to experiencing emotional distress and low levels of happiness due to limited affective support. This study aims to test the effectiveness of emotion regulation training in increasing happiness in 16 adolescents (ages 10–17 years). It was hypothesized that training based on Gross's five stages of emotion regulation would significantly improve happiness scores. Using the one group pretest-posttest design and the Hills & Argyle Happiness Scale, the training was conducted in three sessions (one day). The results of the Paired Sample t-Test showed that although the average happiness score increased marginally from 91.63 (Pretest) to 92.63 (Posttest), the increase was not statistically significant (p = 0.328 > 0.05). These findings provide a theoretical and practical contribution to the need for longer and more intensive intervention durations as input for the design of sustainable programs to improve subjective welfare in orphanages. Keywords: emotion regulation, happiness, orphanage adolescents, subjective well-being, emotion regulation strategies